Virtual learning platform based on WordPress and Moodle to improve the exam evaluation process at the "Bárbara Micarelli" Productive Technical Education Center - Magallán Maslucán, Percy; Santa Cruz Acosta, Roberto Carlos; Maldonado Ramírez, Ítalo; Ríos-Campos, Carlos; Pérez Astonitas, Roberto (Journal of the University of Zulia, 2022)
The research was carried out at the "Bárbara Micarelli" Technical Productive Education Center (CETPRO), located in the district of Jumbilla, Peru. Its objective was to improve the exam evaluation process of this institution, through the use of a virtual learning platform based on WordPress and Moodle; For this, the software engineering methodology XP (Extreme Programming) was used, taking as a sample the 6 teachers of CETPRO "Bárbara Micarelli". Likewise, an applied research was carried out, with a pre-experimental design, based on pre-test and post-test measurements, using data collection techniques such as the survey, as well as time measurements, obtaining as results: mitigation in 58.53% of the time average formulation of evaluations; mitigation in 42.99% of the average time to organize study materials; and the 52.10% increase in the degree of satisfaction of the teachers for the exam evaluation process; thus concluding that the virtual learning platform improved the exam evaluation process.